2016
DOI: 10.1177/1049909116641274
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Delirium Among Patients Having Cancer Injected With Different Opioids for the First Time

Abstract: The incidence of delirium after the commencement of fentanyl injection was significantly lower, suggesting that fentanyl is a useful opioid injection drug from the perspective of delirium risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
1
4
0
1
Order By: Relevance
“…This is consistent with our previous finding 8 that intravenous morphine and oxycodone cause delirium at comparable rates when used as the first opioid. However, we did find that incidence of delirium was lower with the oral formulation than with the intravenous formulation for both morphine and oxycodone (morphine PO in this study vs IV in previous study = 4.8% vs 28.9%, oxycodone PO in this study vs IV in previous study = 6.9% vs 19.5%).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with our previous finding 8 that intravenous morphine and oxycodone cause delirium at comparable rates when used as the first opioid. However, we did find that incidence of delirium was lower with the oral formulation than with the intravenous formulation for both morphine and oxycodone (morphine PO in this study vs IV in previous study = 4.8% vs 28.9%, oxycodone PO in this study vs IV in previous study = 6.9% vs 19.5%).…”
Section: Discussionsupporting
confidence: 93%
“…In 2017, we investigated the incidence of delirium in patients receiving intravenous opioids for cancer pain and found that the incidence was significantly lower with intravenous fentanyl citrate compared with intravenous morphine hydrochloride. 8 In addition, Morita et al 3 found that opioid rotation to fentanyl significantly reduced the severity of delirium in cancer patients with morphine-induced delirium.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Paradoxically, exposure to opioids in hospitalized or cancer patients was significantly associated with an increased risk of delirium. [26][27][28][29] However, Nandi et al 30 found that opioids did not increase the risk of delirium in total joint arthroplasty. Another study performed in a surgical context reported that tramadol and meperidine were associated with an increased risk of delirium but use of morphine, fentanyl, oxycodone, and codeine were not.…”
mentioning
confidence: 99%
“…In this study, 40% of opioid-using patients received fentanyl. Tanaka et al compared the incidence of delirium among patients using various opioids [17].…”
Section: Discussionmentioning
confidence: 99%